Current Status of Cystic Fibrosis in Türkiye: Data from the National Registry - Tural, Dilber Ademhan; Eyuboglu, Tugba Sismanlar; Cinel, Guzin; Cakir, Erkan; Pekcan, Sevgi; Ozcelik, Ugur; Dogru, Deniz (Galenos Publ House, 2025)
OBJECTIVE: The Cystic Fibrosis Registry of T & uuml;rkiye (CFRT) was established by the Turkish Pediatric Respiratory Diseases and Cystic Fibrosis Society and has provided detailed information on demographic, clinical, genetic, and treatment-related aspects of cystic fibrosis (CF) patients since 2017. We aimed to describe the current status of CF in T & uuml;rkiye using CFRT's 2023 annual data. MATERIAL AND METHODS: Demographic, clinical, and treatment data were taken from CFRT's 2023 record. RESULTS: In 2023, 2,258 patients from 34 centers were recorded. The median age of patients was 9.1 years, and 46.9% were female, with a median age at diagnosis of 0.3 years. Only 14.9% of the patients were older than 18 years. Genetic analyses were completed in 97.3% of patients. The most common variant, F508del, had a total variant frequency of 22.1%. The median percent predicted FEV1 and FVC were 88.0 and 94.0 in those aged 6-17 years 71.0 and 84.0 in those aged >= 18 years, respectively. The median values of body mass index z-scores were-0.5, and-0.5 for patients 2-18 and older than 18 years, respectively. Chronic colonization with Pseudomonas aeruginosa was present in 17.2% of the patients. Most patients used inhaled recombinant human DNase (87.1%) and oral pancreatic enzyme replacement treatment (83.0%). CF transmembrane conductance regulator (CFTR) modulators were used by 15.9% of patients. Over the year, 24 patients died, with a median age at death of 13.3 years. CONCLUSION: The CFRT report provides a valuable resource showing the clinical and laboratory data of patients with CF in the country.
Keywords: Cystic fibrosis; Cystic Fibrosis Registry of T & uuml;rkiye; annual data